PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA DAERAH PADA KABUPATEN DAN KOTA DI PROVINSI SUMATERA BARAT - Nelly Prima Putri (Ensiklopedia Social Review, 2021)
This research aimed to examine the effect of Local Revenue and General Allocation Fund to the Regional Expenditure. Independent variable used are Local Revenue and General Allocation Fund, while the dependent variable is Regional Expenditure. The collected data was analyzed using a statistical model of multiple linear regression analysis by using the data obtained from Government Finance Statistics of West Sumatera in 2011 to 2013. In selecting the sample, using census technique and give off 57 sample consist of 12 districts and 7 cities. The result indicate that Local Revenue had significantly influence the Regional Expenditure. The General Allocation Fund had significant effect on Regional Expenditure. Local Revenue together with General Allocation Fund also significantly influenced the Regional Expenditure.